Criticizing Childfree in the View of Radical Libertarian and Cultural Feminism: Maqāṣid al-Sharī‘ah Perspective - Luciana Anggraeni; R. Tanzil Fawaiq Sayyaf; Wanda Izzuqia Airlangga; Siti Syahirah Saffinee (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research examines the childfree decision made by Gita Savitri and her partner through the lens of radical feminism and Islamic jurisprudence, specifically the Maqāṣid al-Sharī‘ah (higher objectives of Islamic law) as outlined by Imam al-Syatibi. The phenomenon of childfree is explored in relation to the feminist concepts of libertarian radical feminism and cultural radical feminism, alongside Islamic perspectives on family and reproduction. purpose of this study is to ascertain how these viewpoints support or contradict the maqasid al-shari'ah, especially the fundamental Islamic legal precepts of life preservation (hifzh nafs) and offspring preservation (hifzh nasl). To collect pertinent data, a variety of books, articles, and journals are read as part of the qualitative research methodology, which is based on a library research strategy. Depending on the feminist and Islamic perspectives used, the finding may indicate that different people have varied opinions about childfree choices.1) Cultural radical feminists could interpret childfree options as a rejection of traditional femininity and authority. 2) Whereas libertarian feminists see them as a way for women to achieve their own emancipation. 3)Although having children is highly regarded in the Islamic framework, women's liberty may be respected without completely abandoning Islamic family and ancestry-related beliefs if society norms and individual choice are balanced.